The 5 Essential People Skills : How to Assert Yourself, Listen to Others, and Resolve Conflicts - Dale Carnegie Training (London Simon & Schuster, 2009)
The business leaders and trainers from Dale Carnegie Training have discovered that applying appropriate assertiveness to all your interactions is the most effective approach to creating a successful career. The 5 Essential People Skills will help you be the most positively assertive, prosperous and inspired professional you can be.
Keywords: Assertiveness (Psychology) -- Interpersonal communication -- Communication